Pelatihan Fotografi Dasar Menggunakan Telepon Genggam Untuk Meningkatkan Kapasitas UMKM Pulo Geulis - Setiawati, Titin; Prasetya, Hendri; Amrillah, Rizki (Jurnal Pustaka Dianmas, 2023)
Small and Medium Enterprises (MSMEs) are one of the business sectors that are resilient in facing challenges and various situations. One of them is when facing the Covid-19 pandemic, small and medium scale businesses have been able to survive and many have developed through marketing through online media. Unfortunately, small and medium enterprises are often not supported by business and marketing structures that can keep up with the times due to capital and human resource constraints. Small and Medium Enterprises in RW 04 Pulo Geulis, Babakan Pasar, Bogor are facing the problem of not having good and attractive product photos that can be used as a means of supporting sales through online media. This training is aimed at providing good and attractive product photography skills for UMKM Pulo Geulis, Babakan Pasar, Bogor so that they can make maximum sales in online media which will increase economic income. The training was attended by 25 people from 5 RTs and received good responses from the participants who stated that this training was very useful and helpful.